Implementation of Protection for Child Victims of Sexual Violence in the City of Surakarta - Aldi Setiawan; Muchamad Iksan (Proceeding International Conference Restructuring and Transforming Law, 2023)
The purpose of writing research using empirical juridical methods is to find out the types of sexual violence, its implementation and also the constraints and efforts on children that occur in the city of Surakarta. The juridical method is by examining secondary data. The results of this study are that there are 15 types of cases of sexual violence against children with domestic violence at their peak with the implementation of legal protection based on the law and under the auspices of the apparatus and related agencies. The difficulty of finding witnesses for the protection of victims of child abuse is an obstacle for the parties involved. Efforts that can be made in this regard development of a model for handling child victims of sexual violence based on local wisdom values in Surakarta, namely trauma healing and family healing as a means of releasing the burden resulting from the presence of victims of sexual violence.